Red blood cell spacing in capillaries of rat heart. - Silverman, David A. (University of Ottawa (Canada), 1996)
Theoretical studies have demonstrated a pronounced effect of red blood cell (RBC) spacing on tissue oxygen supply. In spite of this, realistic values for RBC spacing and related capillary hematocrit (Hct) are not known in the heart. One of the possible reasons is the lack of proper methodology. Thus, the goal of this research study was twofold: (i) to develop a method to rapidly freeze rat heart in situ, following which RBCs and capillary walls could be simultaneously visualized, and (ii) to apply this methodology in rat hearts to establish whether differences exist in capillary Hct and RBC spacing in two distinct locations within the capillary bed, in the subendo- and midmyocardium, during diastole or systole. The results of this study suggest that different geometrical conditions (e.g. RBC spacing and capillary Hct) exist at the two distinct locations of the capillary bed studied. Presumably, the oxygen supply conditions in distal portions of the capillary bed are improved by these geometrical adjustments, preventing hypoxic or anoxic conditions in the tissue, which would be detrimental to cardiac function. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.